2020
DOI: 10.1007/s00408-020-00346-1
|View full text |Cite
|
Sign up to set email alerts
|

Can a New Scoring System Improve Prediction of Pulmonary Hypertension in Newly Recognised Interstitial Lung Diseases?

Abstract: Introduction Pulmonary hypertension (PH) is a well-recognised complication of interstitial lung diseases (ILD), which worsens prognosis and impairs exercise capacity. Echocardiography is the most widely used, non-invasive method for PH assessment. The aim of our study was to identify the factors predictive for echocardiographic signs of PH in newly recognised ILD patients. Methods Ninety-three consecutive patients (28F/65M) with different ILD were prospectively evaluated from January 2009 to March 2014. Pulmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…In addition to the factors of enlarged pulmonary vessels, the subsequent enlargement of the atria and ventricles may lead to the displacement of lung tissue within the thoracic cavity and affect the lung volume [ 32 ]. Most studies show that FEV1/FVC is normal in group I of PH [ 33 ]. This study showed that 95% of patients with CTD-PAH had an FEV1/FVC above 70%.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the factors of enlarged pulmonary vessels, the subsequent enlargement of the atria and ventricles may lead to the displacement of lung tissue within the thoracic cavity and affect the lung volume [ 32 ]. Most studies show that FEV1/FVC is normal in group I of PH [ 33 ]. This study showed that 95% of patients with CTD-PAH had an FEV1/FVC above 70%.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, multivariable analysis has generally led to the verification of this observation and to multiple algorithms incorporating a selected set of measurements (BNP, DLCO, echocardiography), 55 (Ratio of FVC/DLCO, PAA, RVSP) 56 (TLC/DLCO index, age, 6MWD, room air oxygen saturation at 6MW). 57 In absence of established research, a combination of these methods could be used to lead clinicians from routine history, examinations, and laboratory findings to a primary workup for PH with echocardiography, 6MWD measurements, and BNP/NT-proBNP, with a low threshold for RHC in the right clinical setting. (See Table)…”
Section: Diagnosis Screening and Monitoringmentioning
confidence: 99%
“…However, it is expensive, invasive, and associated with several complications, 8 Echocardiography is the most widely used and recommended non-invasive method for assessing PH. 9 Compared to RHC, echocardiography has been shown to be a reliable method in several studies. 10 , 11 In the 2015 European Society of Cardiology (ESC)/European Respiratory Society (ERS) Guidelines for the Diagnosis and Treatment of Pulmonary Hypertension, echocardiography is the preferred non-invasive test for PH screening and follow-up; the guidelines also recommend that it should be used to screen for PH in patients whose clinical data suggest an increased risk of PH.…”
Section: Introductionmentioning
confidence: 99%